Salting-out effect promoting highly efficient ambient ammonia synthesis - Mengfan Wang (Nature Portfolio, 2021)
The electroreduction of nitrogen to ammonia offers a promising alternative to the Haber–Bosch process but suffers from low activity and selectivity. Here, authors demonstrate that triggering a salting-out effect in a highly concentrated electrolyte can achieve highly efficient ammonia synthesis.